1991
DOI: 10.1093/oxfordjournals.jpart.a037081
|View full text |Cite
|
Sign up to set email alerts
|

Policy Entrepreneurs: Their Activity Structure and Function in the Policy Process

Abstract: "Public entrepreneurship" is the process of introducing innovation--the generation, translation, and implementation of new ideas-into the public sector. The research described here focuses on "policy entrepreneurs." These are public entrepreneurs who, from outside the formal positions of government, introduce, translate, and help implement new ideas into public practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 23 publications
0
44
0
Order By: Relevance
“…There are several common tactics that policy entrepreneurs use when framing problems. Among other things, these tactics include presenting evidence in ways that suggest a crisis is at hand (Nelson 1984;Stone 1997), finding ways to highlight failures of current policy settings (Baumgartner andJones 1993/2009;Henig 2008), and drawing support from actors beyond the immediate scope of the problem (Levin and Sanger 1994;Roberts and King 1991;Schattschneider 1960). Recent work by Dewulf and Bouwen (2012) has emphasized the interactional nature of problem framing.…”
Section: Problem Framingmentioning
confidence: 99%
“…There are several common tactics that policy entrepreneurs use when framing problems. Among other things, these tactics include presenting evidence in ways that suggest a crisis is at hand (Nelson 1984;Stone 1997), finding ways to highlight failures of current policy settings (Baumgartner andJones 1993/2009;Henig 2008), and drawing support from actors beyond the immediate scope of the problem (Levin and Sanger 1994;Roberts and King 1991;Schattschneider 1960). Recent work by Dewulf and Bouwen (2012) has emphasized the interactional nature of problem framing.…”
Section: Problem Framingmentioning
confidence: 99%
“…McCaffrey and Salerno (2011) argued that those who sit outside government can be better positioned to shape government agendas than those inside. Roberts and King (1991), in their study of the activity structure and function of entrepreneurs in the policy process, have argued that policy entrepreneurs are, by definition, outside actors (p. 152). Davies and True (2017), in their examination of the case of former British foreign secretary William Hague as an unlikely advocate for the prevention of sexual violence in conflict, found that the positioning of norm entrepreneurs "outside of conventional power" and networks, often enables them to "connect existing interests and resources with a moral prerogative, establish strong organizational platforms, and leverage networks" (p. 705).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that elite or high-level entrepreneurs are more likely to successfully influence policy design (e.g., Baker & Steuernagel, 2009;Roberts & King, 1991;Ugur & Yankaya, 2008;Zhu, 2012). Although the existing literature regarding "street-level policy entrepreneurship" has criticized research on high-level policy entrepreneurs for not giving enough importance to the policy entrepreneurship of SLBs, these critiques ignore the possibility of a social worker being an elite.…”
Section: Strategy 1: Social Workers As Actual Political Elites At Grassrootsmentioning
confidence: 99%